2011
DOI: 10.1103/physrevd.84.023004
|View full text |Cite
|
Sign up to set email alerts
|

Bulk viscosity coefficients due to phonons and kaons in superfluid color-flavor locked quark matter

Abstract: We evaluate the three bulk viscosity coefficients 1 , 2 and 3 in the color-flavor locked superfluid phase due to phonons and kaons, which are the lightest modes in that system. We first show that the computation is rather analogous to the computation of the same coefficients in superfluid 4 He, as due to phonons and rotons. For astrophysical applications, we also find the value of the viscosities when there is a periodic disturbance, and the viscosities also depend on the frequency of the disturbance. In a tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, the dominant contribution to the bulk viscosity may come from processes involving the neutral kaon K 0 [37,40,41]. For temperatures above a few MeV, the bulk viscosity ζ K 0 can become larger than for unpaired quark matter, but at low temperatures ζ K 0 is much less than that of unpaired quark matter (see also [42]). As a consequence, for cold enough objects we may expect that the fundamental mode will be damped only by gravitational radiation, and the determination of the frequency and damping time of the fundamental mode could be a promising way to constrain the properties of CFL strange stars.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dominant contribution to the bulk viscosity may come from processes involving the neutral kaon K 0 [37,40,41]. For temperatures above a few MeV, the bulk viscosity ζ K 0 can become larger than for unpaired quark matter, but at low temperatures ζ K 0 is much less than that of unpaired quark matter (see also [42]). As a consequence, for cold enough objects we may expect that the fundamental mode will be damped only by gravitational radiation, and the determination of the frequency and damping time of the fundamental mode could be a promising way to constrain the properties of CFL strange stars.…”
Section: Discussionmentioning
confidence: 99%
“…This effective theory does not tell us if and at what density CFL is replaced by another phase, but it can be used to compute properties of CFL and CFL- in terms of a small number of unknown couplings in the Lagrangian. This has been done for transport properties such as bulk and shear viscosities [ 2373 , 2390 2392 ]. Since its form is determined by the symmetries of CFL, the effective theory must be valid for all densities where CFL, or any other phase with the same symmetry breaking pattern, exists (at energies far below the critical temperature of CFL).…”
Section: Nuclear Physics and Dense Qcd In Colliders And Compact Starsmentioning
confidence: 99%
“…In quark matter, only the CFL phase (and its variants) is superfluid, because of the spontaneous breaking of baryon number conservation, see ( 7.4 ). Superfluidity of the CFL phase manifests itself-for instance in the presence of three different bulk viscosity parameters [ 2392 ].…”
Section: Nuclear Physics and Dense Qcd In Colliders And Compact Starsmentioning
confidence: 99%
“…In the case of astrophysical phenomena, the bulk viscosities are calculated for periodic perturbations, leading the system away from equilibrium. In [30], it was shown that:…”
Section: Bulk Viscositiesmentioning
confidence: 99%